Recording Messages on Nonplanar Objects by Cryogenic Electron‐Beam Writing. (7th March 2022) - Zheng, Rui; Zhao, Ding; Lu, Yihan; Wu, Shan; Yao, Guangnan; Liu, Dongli; Qiu, Min
Abstract: The evolution of writing systems illustrates the development of information storage. Here, a unique way is demonstrated using sprayed anisole as the ink and a focused electron‐beam as a pen to record messages on a cooled substrate. Such an electron‐beam writing approach controls the thickness of remained anisole on the substrate. Optical interference at the visible region occurs thereby, resulting directly in a color print. Using discrete dose distribution, an 11‐step structure with a height difference of sub‐10 nm accuracy is written. A quinary pattern with a total thickness of 180 nm and unit square size of 500 nm is also written, implying information density beyond 10 13 bits per cm 3 (10 Tbit cm –3 ). Painting at the nanoscale is also enabled by importing grayscale images. In addition, the substrate can be extended from planar to nonplanar or flexible objects, such as an aluminum tape or a silver wire. Combining the grayscale lithographic nature and conformal coating of the ink, this writing process has great potential to store information on any surface. Abstract : Benefiting from 3D grayscale lithography and conformal covering of sprayed "organic ink, " stepped structures with an accuracy of sub‐10 nm in height are written by using a focused electron‐beam as a pen, leading to information storage or high‐resolution painting on nonplanar objects.